A Heater-Assisted Air Source Heat Pump Air Conditioner to Improve Thermal Comfort with Frost-Retarded Heating and Heat-Uninterrupted Defrosting - Fei Wang; Rijing Zhao; Wenming Xu; Dong Huang; Zhiguo Qu (Energies, 2021)
Frost deposits on the outdoor heat exchanger of an air source heat pump (ASHP) air conditioner and reduces its capacity during winter operation. However, the prevailing reverse-cycle defrosting (RCD) turns the indoor heat exchanger into an evaporator and ceases heat supply to the living space. Consequently, the thermal comfort for indoor occupants is deteriorated. This article proposes a heater-assisted ASHP to tackle this problem. With an 800 W electromagnetic heater equipped upstream of the outdoor heat exchanger to provide refrigerant with additional heat, the ASHP retarded frost under original throttling control and compressor speed during the heating cycle (frostless mode), and even removed frost with uninterrupted heat supply to indoor space under little throttling and reduced compressor speed (anti-frost mode). Compared with the original operation of the ASHP when the heater was off (baseline mode), frostless and anti-frost modes extended heating duration by 17.9% and 99.7%, respectively, with comparative time-averaged supply-air temperature. Moreover, COP for baseline and anti-frost modes was similar by average, about 3% higher than for the frostless mode. Further optimizations will be done on the co-adjustment of throttling control and compressor speed to better fulfill the potential of the heater-assisted ASHP.